Integrating cavity based gas cells: a multibeam compensation scheme for pathlength variation - Bergin, Sarah; Hodgkinson, Jane; Francis, Daniel; Tatam, Ralph P. (Cranfield University, 2016)
Data to support the following paper: Integrating cavity based gas cells: a multibeam compensation scheme for pathlength variation S Bergin, J Hodgkinson, D Francis and R P Tatam Optics Express 24 (12), 13647 - 13664, 2016 doi:10.1364/OE.24.013647
Keywords: Integrating spheres'; 'Absorption spectroscopy'; 'Laser diodes'; 'Gas sensing'; 'Engineering Instrumentation'; 'Photodetectors; Optical Sensors and Solar Cells'; 'Photonics and Electro-Optical Engineering (excl. Communications)'